Proteinuria as a significant predictive factor for the progression of carotid artery atherosclerosis in non-albuminuric type 2 diabetes - Kim, Young-eun; Lee, Minyoung; Lee, Yong-ho; Kang, Eun Seok; Cha, Bong-soo; Lee, Byung-Wan (Diabetes research and clinical practice, 2021)
•A high urine protein-to-creatinine ratio may be a useful and early predictive marker for the progression of carotid artery atherosclerosis , even in patients with type 2 diabetes and without albuminuria.•A high urine protein-to-creatinine ratio may be an earlier indicator of DKD development than albuminuria, suggesting renal tubulopathy.•A retrospective study included 927 participants with type 2 diabetes and without albuminuria. This study aimed to evaluate the clinical significance of urine protein to creatinine ratio (uPCR) in relation to the cardiovascular risk associated with carotid artery intima-media thickness (cIMT) progression in subjects with type 2 diabetes (T2D) and normoalbuminuria. In this retrospective longitudinal study on T2D, we recruited 927 participants with normoalbuminuria (urine albumin to creatinine ratio [uACR] < 30 mg/g) whose cIMT was measured at baseline and after at least 1 year, and whose initial uPCR and uACR data were available. Higher initial uPCR was positively correlated with a greater increment in maximal cIMT (β = 0.074, p = 0.028), and this correlation was significant even after adjusting for multiple confounding factors (β = 0.074, p = 0.046). High baseline uPCR was an independent predictive factor for the increased risk of maximal cIMT progression in a simple logistic regression model (OR, 1.41; 95% CI, [1.08–1.86]; p = 0.013). Even after adjusting for several confounding variables, higher uPCR was significantly associated with a higher risk of cIMT progression (OR, 1.48; 95% CI, [1.08–2.03]; p = 0.014). These results suggest that high uPCR may be a useful predictive marker for the progression of carotid artery atherosclerosis, even in subjects with T2D and without albuminuria.